Railroads, technology adoption, and modern economic development: Evidence from Japan - Junichi Yamasaki (Osaka University, Institute of Social and Economic Research (ISER), 2017)
Railroad access can accelerate the technological progress in the industrial sector and therefore induce structural change and urbanization, the two common features of modern economic growth. I examine this particular mechanism in the context of Japanese railroad network expansion and modern economic growth in the late 19th century and early 20th centuries. By digitizing a novel data set that measures the use of steam engines at the factory level, allowing me to directly observe the diffusion of steam power, I analyze the effect of railroad access on the adoption of steam power. To overcome the endogeneity problem, I determine the cost-minimizing path between destinations, and use this to construct an instrument for railroad access. I find that railroad access led to an increased adoption of steam power by factories, which in turn reallocated labor from the agricultural to the industrial sector, thereby inducing structural change. Railroad network also broke mean reversion in population growth, eventually leading to urbanization. My results support the view that railroad network construction was key to the modern economic growth in pre-First World War Japan.
Additional information: The 19th ISER-Moriguchi Prize (2016) Awarded Paper.
Keywords: N65; N75; O14; O18; O33; 330; Railroads; Transportation Infrastructure; Technology Adoption; General Purpose Technology; Structural Change; Urbanization